The use of permutation representations in structural computations in large finite matrix groups. (November 2019) - Cannon, John J.; Holt, Derek F.; Unger, William R.
Abstract: We determine the minimal degree permutation representations of all finite groups with trivial soluble radical, and describe applications to structural computations in large finite matrix groups that use the output of the CompositionTree algorithm. We also describe how this output can be used to help find an effective base and strong generating set for such groups. We have implemented the resulting algorithms in Magma, and we report on their performance.